Ammonia ambiance induces SIRT5 regulated expression of EGF-AKT-mTOR axis in Asian stinging catfish Heteropneustes fossilis (Bloch) 1974 - Chowdhury, Sabarna; Saikia, Surjya K (Acta Biologica Szegediensis, 2022)
The present study was aimed to understand whether ammonia exposure induces oxidative stress in Heteropneustes fossilis and what is the fate of the excess ammonia in the skeletal muscle of the fish. The experiments were performed in two different sets as control and treated (repeated three times with fresh specimens) of aquaria with 25 mM of ammonium chloride treatment and the tissues were collected in different time intervals (24 h, 72 h and 7 days). The collected tissues were studied to understand the change of SIRT5 levels in liver and skeletal muscle tissues. The results that were obtained from investigation of MDA (malondialdehyde) and superoxide dismutase (SOD) revealed that the fish undergoes extensive oxidative stress when exposed to ammonia ambiance. Further, after 7 days of ammonia exposure increase in the levels of glutamate and glutamine revealed the fate of excess ammonia in the skeletal muscle of the fish. Moreover, the levels of cell proliferator proteins like EGF, AKT and mTOR were also analysed and found an increase in their expression with a time dependent manner. It indicates that the excess ammonia could be utilised in synthesising protein and triggering cell growth and proliferation even under such harsh condition of ambient ammonia.